Interpolating South Asian Transnational Heritage: Allegory In South Asian Diasporic Metropolitan Young Adult Fiction - Rasagam, Manohari; Pillai, Shanthini (Penerbit Universiti Sains Malaysia (USM Press), 2016)
Young adult books written by western metropolitan authors clearly cater to a western audience: the protagonists, settings and the archetypes of these texts are Eurocentric. Eurocentric concepts and experiences are often assumed to be universal. This could result in the othering of the non-white imaginary within young adult fiction. However, multicultural young adult texts are increasingly available on the global market. This paper investigates a selection of young adult fiction written by authors of the South Asian diaspora to determine whether the use of allegory in the form of cultural myths and folklore drawn from an ancestral cultural repertoire allows these texts to insert themselves into and dismantle the hegemony of metropolitan Eurocentricism in the consciousness of the diasporic South Asian reader. To explore this possibility, the following works of South Asian diasporic metropolitan young adult fiction are analysed: Dahling If You Luv Me Please Please Smile (1999) by Rukhsana Khan; Bindi Babes by Narindher Dhami (2005); and Blue Boy (2009) by Rakesh Satyal. This study focuses on the ways in which the authors of these texts interpolate a South Asian transnational heritage into the setting of the metropolitan public school, especially through the allegorical mode. The ultimate aim of this paper is to demonstrate that the incorporation of South Asian cultural myths and folklore into settings familiar to young adult readers can contribute to generating awareness of the cultural heritage of diasporic youth.